Investigation of the Hot Deformation Behavior in VDM® Alloy 780 by In Situ High-Energy X-Ray Diffraction - Fritton, Massimo; Kümmel, Frank; Kirchmayer, Andreas; Stark, Andreas; Hafez Haghighat, Masood; Gehrmann, Bodo; Neumeier, Steffen; Gilles, Ralph (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Ni-based superalloys are indispensable for applications in demanding environments, such as the heavily stressed rotating discs in the hot sections of modern gas turbines or jet engines. In this paper, the microstructure evolution during hot deformation to mimic the forging process was investigated in the polycrystalline VDM® Alloy 780 viain situ X-ray diffraction at temperatures of 950, 1000, and 1050 °C. For the tested temperatures, the hot forming led to subgrain formation, the built-up of a texture by rotation of the matrix grains into preferred orientations, and dynamic recrystallization. The influence of the deformation was analyzed depending on the direction of the lattice plane normals to the load direction, for the first five γ-reflections in the diffraction pattern. During uniaxial compressive deformation intensity, maxima develop in the loading direction solely for the γ-(220) reflections, while intensity minima develop for the other reflections which correspond to the formation of a <110> fiber texture. In the transverse direction, all γ-reflections except the (220) have an increased intensity at the maximum specimen strain of 20 pct. Directly after the hot forming, three different cooling rates of 10, 100, and 1000 °C/min and their influence on the microstructure were investigated. The fast and medium cooling rates lead to low recrystallized fractions and a largely preserved deformation texture, whereas the low cooling rate leads to a high recrystallized fraction and a slight remaining texture. Additionally, the diffraction data are complemented by electron microscopy measurements.
CRIS-Team Scopus Importer:2023-01-27